The dynamics of biochemical parameters in blood of clinically healthy Holstein cows from day 5 before to day 60 after calving - Celeska Irena, Janevski A., Dzadzovski I., Ulchar I., Kirovski Danijela (Macedonian Veterinary Review, 2015)
The peripartal period in Holstein dairy cows is critical, due to the transition from pregnancy to lactation. We have studied the dynamics of biochemical parameters from day 5 before to day 60 after calving. The study included 10 multiparous Holstein cows, examined at days -5, 5, 10, 30 and 60 relative to calving. Blood samples were taken from vena jugularis. Analyzed biochemical parameters were glucose, triglycerides, total cholesterol, total bilirubin, albumin, total protein, urea, NEFA and BHBA. Milk production and body condition score were also estimated. Obtained results showed that cows were exposed to mild to marked metabolic distress. Energy status was changed due to increased values of NEFA and BHBA and decreased value of glucose after calving. Protein concentrations were increased at day 10 after calving, despite the decrease of the level of albumin. Urea concentrations before and after calving were within physiological range indicating an optimal protein diet. Increased values of total bilirubin at day 5 after calving indicated liver increased activity. Lipid status presented by triglycerides and total cholesterol revealed no differences in blood concentrations. Milk production was highest at day 30 after calving. BCS were highest in dry cows, thereafter they declined and recovered at day 60 after calving. In conclusion, biochemical parameters can be used as relevant indicators of metabolic distress in cows around calving with milk and BCS recording as aside parameters. Changes in some biochemical parameters indicate liver increased activity and metabolic stress, that could lead to decreased milk production, impaired reproductive performance and, finally, to illness.
Keywords: Holstein cows, biochemical parameters, transition period